Implementation of Six Sigma in Glucose POCT Quality Control at Dr. Soetomo General Academic Hospital - Susi Oktaviani; M. Robiul Fuadi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Point of Care Testing (POCT) is important for the examination of critically ill patients in the emergency room and intensive care unit. The evaluation of the analytic quality of POCT is needed to ensure the quality of patient care at Dr. Soetomo General Academic Hospital. The purpose of this study is to evaluate the analytical quality of POCT at Dr. Soetomo General Academic Hospital. This was an observational analytical study that was done at Dr. Soetomo General Academic Hospital Surabaya in July 2017. Point of care testing quality analysis was based on 20 within run Internal Quality Control (IQC). Internal quality control data was used to calculate the mean, SD, and CV%. CV% was calculated with the following equation "CV%=(SD í— 100)/mean". Bias % = [ control mean – control true value]/control true value x 100. The sigma value was obtained from Total Error Allowance (TEa) – Bias/CV. TEa in this study was based on ISO 15197:2003. The results of the glucose examination (58 samples) from Dimension EXL 1, 2, 3 (hexokinase method) compared with 7 glucose POCT (glucose oxidase:i-STAT Nova Biomedical method). The correlation was calculated with Spearman statistical analysis using the SPSS version 23.0. the mean CV of seven POCTs=3.5% (1.7%-5%), mean bias of seven POCT=7.75% (4.8%-12.5%), the mean six sigma of 7 POCT=6.77 (4.0–11.6). The best POCT with a six sigma value of > 6 was glucometer K14_2, Palem 1 and GRIU. The glucometer with the lowest six sigma values but still had good quality control were K14_1 and ROI. All glucometers had a good correlation with r value > 0.8 (p=0.000). Glucose POCT in Dr. Soetomo General Academic Hospital all had good quality and met world-class standards. Further study using IQC 2 levels is recommended for a better POCT quality evaluation.